A Transfer of Leadership Competencies: Theories, Mechanism and Barriers - Swoiński, Łukasz (Journal of Positive Management, 2026)
Purpose: The aim of the article is to analyze the possibilities of transferring leadership competencies developed in the military environment to civilian organizations. Design/methodology/approach: The study is based on a critical review of the literature in the field of leadership theory, military leadership, competency transfer, and organizational adaptation. The article identifies key competencies developed in the military context, including decision-making under pressure, crisis management, psychological resilience, mission orientation, and effective communication. Particular attention was devoted to mechanisms facilitating competency transfer as well as structural, organizational, and personal barriers limiting their adaptation in the civilian environment. Fidings: The analysis indicates that leadership competencies developed in the military possess significant transfer potential, especially in organizations operating under conditions of volatility, uncertainty, complexity, and ambiguity (VUCA). At the same time, the transfer process does not occur automatically and requires both the adaptive abilities of the individual and appropriate organizational support mechanisms, such as mentoring, onboarding programs, and competency validation systems. Originality/value: The article contributes to the literature by integrating perspectives from leadership research, military studies, and learning transfer theory within a coherent analytical model. The results of the analysis indicate that the effective utilization of the leadership competencies of former military leaders may strengthen organizational resilience, improve crisis response capabilities, and support the development of adaptive leadership in civilian organizations.